SWOT-Based Marketing Strategy Development for Puli Crackers MSME Fitri: Pengembangan Strategi Pemasaran Berbasis SWOT untuk Puli Crackers UMKM Fitri - Fachrudin, Mochamad Fais; Wahyuni, Hana Catur (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Small and Medium Enterprises (MSMEs) play a vital role in supporting Indonesia’s local economy, particularly in the food processing sector. Specific Background: The Puli Crackers MSME “Fitri” in Mojokerto has experienced production stability but limited market expansion due to intense competition and inconsistent quality control. Knowledge Gap: Prior efforts have focused on operational efficiency, with little emphasis on integrated marketing strategy formulation based on internal and external factors. Aims: This study applies SWOT and QSPM methods to design strategic alternatives for marketing development at the MSME. Results: The analysis identified strengths in product quality and customer loyalty, weaknesses in promotion and digital branding, opportunities in e-commerce growth, and threats from price competition. The QSPM matrix recommends a “Market Penetration and Product Diversification” strategy with the highest attractiveness score (TAS = 6.21). Novelty: Combining SWOT–QSPM with qualitative validation through owner interviews provides a structured, quantitative approach to MSME strategic planning. Implications: The study highlights how local food industries can leverage digital marketing and partnership expansion to sustain growth in competitive markets.